2018
DOI: 10.1111/jrh.12297
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Stakeholders in the Development of an eHealth Intervention for Cancer Symptom Management for Rural Residents

Abstract: Patients (n = 16) and clinical staff (n = 10) participated in phase 1. Three major themes were identified: "symptom experience," "symptom management," and "technology." Through an iterative process using these results and evidence from the literature, the OASIS web application was developed. Usability testing with N = 126 stakeholders demonstrated that the web application is easy to use, contains relevant content, and has pleasing graphics. No differences were found among patients, family/friends, and staff. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…Compliance was 98% https://ascopubs.org/doi/abs/10.1200/JCO.2018.36.15_suppl.e18883 OASIS (Oncology Associated Symptoms and Individualized Strategies) Yes Web-based app ( https://oasis.nursing.uiowa.edu/AboutOasis ) Monitoring platform to track symptom distress with educational information about cancer symptoms Yes Web-based app Provide self-management strategies for symptoms Feasib. In progress 56 patients; 57 caregivers; 9 HCPs Adult potential system users from rural areas - Easy to use; relevant content (patients and caregivers) - Feasible; easy to use; relevant content Gilbertson-White [ 64 ] Oncokompas Yes Web-based PROMs completion targeting QOL domains Yes Web-based Tailored advice and personalized referral to supportive care options based on PROM scores and expressed preferences. Feasib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance was 98% https://ascopubs.org/doi/abs/10.1200/JCO.2018.36.15_suppl.e18883 OASIS (Oncology Associated Symptoms and Individualized Strategies) Yes Web-based app ( https://oasis.nursing.uiowa.edu/AboutOasis ) Monitoring platform to track symptom distress with educational information about cancer symptoms Yes Web-based app Provide self-management strategies for symptoms Feasib. In progress 56 patients; 57 caregivers; 9 HCPs Adult potential system users from rural areas - Easy to use; relevant content (patients and caregivers) - Feasible; easy to use; relevant content Gilbertson-White [ 64 ] Oncokompas Yes Web-based PROMs completion targeting QOL domains Yes Web-based Tailored advice and personalized referral to supportive care options based on PROM scores and expressed preferences. Feasib.…”
Section: Resultsmentioning
confidence: 99%
“…From the patient perspective, some of the key factors identified for the uptake of the digital tools included the following: Ease of use [ 30 , 38 , 44 , 51 , 53 , 55 , 64 , 80 ]; Reassurance [ 28 , 30 , 41 , 48 , 49 , 55 , 59 , 70 ]; High usability and usefulness [ 37 , 42 , 44 , 58 , 62 , 74 ]; Improved communication with HCPs [ 27 , 29 , 30 , 53 , 58 ] www.owise.uk ; Correct generation of system alerts and fast response to alerts [ 28 , 70 , 80 ]; Patient empowerment [ 29 , 30 , 69 ]; and The convenience of real-time reporting of symptoms [ 28 , 37 ]; …”
Section: Resultsmentioning
confidence: 99%
“…A total of three studies analyzed telehealth interventions in patients and health care professionals. Gilbertson-White et al [ 18 ] examined patient needs and satisfaction with an electronic health tool, Oncology Associated Symptoms and Individualized Strategies (OASIS), and concluded that the web application is easy to use, contains relevant content, has pleasing graphics, and was perceived positively. There were infrequent users of OASIS in the group; however, both frequent and infrequent internet users positively evaluated the web application [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the current state of science on the web and mobile based symptom management interventions for advanced cancer patients which is still in its infancy, we could not include studies that were either ongoing or only had a published protocol. 46,47 Acknowledging that these studies have the potential to move the symptom management interventions forward, there are opportunities for future systematic reviews and meta-analyses once the results of these studies are published and available.…”
Section: Discussionmentioning
confidence: 99%